Pengaruh Kualitas Pelayanan, Dan Kualitas Produk Makanan Terhadap Kepuasan Konsumen Di Restoran Sendok Bebek Semarang - Yustina Denik Risyanti; Ninuk Subandyah; Renny Aprilliyani; Mengku Marhendi; Haniek Listyorini (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
The rapidly growing demand for business actors to always make improvements in all fields, especially the improvement in the service sector and menu innovations that are varied and acceptable to customers. All of these are natural things considering the excellent service implemented by the restaurant, tends to be a comfortable place, good views and cheap menus can attract many customers. A careful planning needs to be done to anticipate the development of existing competitors. Conduct an analysis of the existing market including determining who the competitors are, analyzing their strengths and weaknesses, as well as analyzing the restaurant itself. This research method uses quantitative descriptive, namely collecting, compiling, processing and analyzing data in the form of numbers which in practice are given certain treatment which is studied in it, it is known that the sample size in this study is 96 customers at Eden Daily International Food Semarang. The level of customer satisfaction can be seen from the value of excellent service and product quality, if excellent service can be provided properly and can meet customer expectations and is supported by good product quality and can provide satisfactory customer satisfaction, visiting customers will feel satisfied.